A Catechism For Business - Andrew V. Abela,, Joseph E. Capizzi (Catholic University of America Press, 2014)
The incidence of scandal arising from ethical violations in the business world has been increasing over the past several years. At work, many managers who consider themselves to be faithful are all too willing to â€œcheck their religion at the door,â€ often simply because they are unaware of the implications of their faith for their business practices. The purpose of this book is to help change this state of affairs by presenting the teachings of the Catholic Church as they relate to specific questions in business ethics. Catholic social teaching has been called â€œthe Churchâ€™s bestkept secret.â€ This is especially true of its applications to business. The Catholic Church over the years has developed extensive guidance of great relevance to many areas of business, but this guidance is often buried within lengthy Church documents not easily accessible to the layperson. When faced with specific ethical questions, Catholics may not know where to search for answersâ€”if they even know that such answers exist. The main contribution of this book is to organize in one volume Church teaching of relevance to business and economics by topic and specific question.